Slimy Bhd: Slimy Cleaning Borax / Zarif Luqmani Norzairee...[et al.] - Norzairee, Zarif Luqmani; Alias, Muhammad Haziq; Mat Isa, Muhammad Haziq; Azman, Muhammad Aiman Azhim; Ma'amin, Saibatul Nazmie (2016)
We first began our as a way to profit from our passion and provide others with a safe, easy and economical and friendly cleaning material that may revolutionized cleaning method.